DUKUNGAN PEMERINTAH DAERAH DALAM PENANGANAN ANAK JALANAN DI KOTA PADANG SUMATERA BARAT - Sundayani, Yana (Pekerjaan Sosial, 2016)
Abstract Support local governments (LGs) in the treatment of street children in West Sumatra is to see the institutional capacity of local street children in 2014. The research objectives were to obtain an overview empirically assess and perform a clear analysis related to local government support of Padang in the handling of street children. The study used a qualitative approach using primary and secondary data sources and data collection techniques using the technique of in-depth interviews, participatory observation, study the documentation and Focus Group Discussion (FGD). Data analysis technique used is descriptive qualitative analysis. Engineering samples by purposive sampling as many as 10 informants. The results showed the number of street children in West Sumatra and the 805 children in the city of Padang amounted to 695 children. Street children are the most numerous of the outside area of Padang. West Sumatra government preparedness in order to achieve child-friendly city, can be seen from the cooperation with various parties such as the Department of Education, Office of Population and Civil Registration (Dukcapil), the universities. It is necessary in the cooperation is the improvement of coordination between the units involved in the management of street children. Data base about street children is necessary so as to facilitate in getting data that can be justified on street children. Regulations related to street children in the form of draft Regulation (draft) on the protection of women and children, but there is no special local regulations about street children. Culture in West Sumatra related to local knowledge is a real public participation, but in fact people do not carry local knowledge optimally. Private parties (LSM / NGO) not all participate fully associated with the handling of street children. There is still a lack of human resources, especially of social workers in the field of children. So for handling street children in West Sumatra necessary cooperation and coordination with related work units, a data base of street children, street children associated regulations, application of local wisdom and cooperation with the private sector in handling street children. Expected future can be realized as an area of Padang eligible children. Key words: policy, local governments, street children Abstrak Dukungan pemerintah daerah (Pemda) dalam penanganan anak jalanan di Sumatera Barat adalah untuk melihat kesiapan daerah bebas anak jalanan pada tahun 2014. Tujuan penelitian untuk memperoleh gambaran secara empirik, mengkaji serta melakukan analisis yang jelas terkait dukungan pemerintah daerah Kota Padang dalam penanganan anak jalanan. Penelitian menggunakan pendekatan kualitatif dengan menggunakan sumber data primer dan sekunder dan teknik pengumpulan data menggunakan teknik wawancara mendalam, observasi partisipasi, studi dokumentasi serta Focus Group Discussion (FGD). Teknik analisa data yang digunakan adalah analisis deskriptif kualitatif. Teknik sampel dengan purposive sampling  sebanyak 10 informan.Hasil penelitian menunjukkan  jumlah anak jalanan di Sumatera Barat adalah 805 anak dan di Kota Padang berjumlah 695 anak. Anak jalanan yang paling banyak dari luar daerah Padang. Kesiapan pemerintah Sumatera Barat dalam  rangka mencapai kota layak anak, dapat terlihat dari kerjasama dengan berbagai pihak seperti Dinas Pendidikan, Dinas Kependudukan dan Catatan Sipil (Dukcapil), dan pihak perguruan tinggi. Hal yang diperlukan dalam kerjasama  adalah peningkatan koordinasi antara unit kerja yang terkait dalam penanganan anak jalanan. Data base tentang anak jalanan merupakan hal yang diperlukan sehingga memudahkan dalam mendapatkan data yang dapat dipertanggungjawabkan tentang anak jalanan. Peraturan yang terkait anak jalanan dalam bentuk Rancangan Peraturan Daerah (Raperda) tentang perlindungan perempuan dan anak, tetapi belum ada peraturan daerah  yang khusus tentang anak jalanan. Budaya di Sumatera Barat yang berkaitan dengan kearifan lokal merupakan peran serta masyarakat secara nyata, namun dalam kenyataan masyarakat belum melaksanakan kearifan lokal secara optimal. Pihak-pihak swasta (LSM/ NGO) belum semuanya berpartisipasi secara penuh terkait dengan penanganan anak jalanan. Masih kurangnya sumber daya manusia khususnya dari pekerja sosial di bidang anak. Sehingga untuk penanganan anak jalanan yang ada di Sumatera Barat diperlukan kerjasama dan koordinasi dengan unit kerja terkait, data base anak jalanan, peraturan yang terkait anak jalanan, penerapan kearifan lokal serta kerjasama dengan pihak swasta dalam penanganan anak jalanan. Diharapkan kedepan dapat terwujud Kota Padang sebagai daerah layak anak. Kata kuci: kebijakan, pemerintah daerah, anak jalanan